European coasts of Bohemia negotiating the Danube-Oder-Elbe canal in a troubled twentieth century - Janáč, Jiří 1978- (Technology and European history series, 2020)
The Danube-Oder-Elbe Canal promised to create an integrated waterway system across Europe, linking Black Sea ports to Atlantic markets and giving landlocked Czech nation its own connections to the ocean. The fascinating history of this never-completed project, 'European Coasts of Bohemia' tells the story of the experts who confronted and contributed to different and often conflicting geopolitical visions of Europe. Jirí Janác shows how the canal-backers adapted themselves to various political developments, such as the break-up of the Austrian-Hungarian Empire and the integration into the Soviet Bloc, while still managing to keep the canal project alive